Design of a printed semi-circular loop antenna - Liu, Feng. (2011)
A semi-circular loop antenna is been printed on a dielectric substrate circuit board and mounted above a finite ground plane. It has a advantage of widening the 10 dB return loss bandwidth by using a mutual electromagnetic coupling effect between a short-circuited printed half loop antenna and an open circuited printed arc monopole line. The monopole line was feed by using a 50 Ω SMA connector.